2012
DOI: 10.1055/s-0031-1298372
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Antispasmodic Effects of the Essential Oil ofOcimum micranthum: Potential Anti-inflammatory Properties

Abstract: The antinociceptive and antispasmodic properties of the essential oil of OCIMUM micranthum (EOOM) were characterized. In mice, EOOM (15-100 mg · kg (-1), p. o.) reduced both the writhing responses induced by acetic acid and the licking-time induced by formalin, being inert on the hot plate test. In rat trachea, EOOM relaxed sustained contractions induced by KCl or carbachol (CCh). Its constituents, ( E)- [( E)-MC] and ( Z)-methyl cinnamate [( Z)-MC], reproduced several effects of EOOM. Inhaled as aerosol, EOOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
19
0
2
Order By: Relevance
“…Cystic Fibrosis patients are often infected by S. aureus, H. influenzae and P. aeruginosa [25]. In another study, the anti-inflammatory property of Ocimum micranthum EO (OMEO) was assessed [26]. In rat trachea, OMEO relaxed contraction induced by carbachol.…”
Section: Animal Trialsmentioning
confidence: 99%
“…Cystic Fibrosis patients are often infected by S. aureus, H. influenzae and P. aeruginosa [25]. In another study, the anti-inflammatory property of Ocimum micranthum EO (OMEO) was assessed [26]. In rat trachea, OMEO relaxed contraction induced by carbachol.…”
Section: Animal Trialsmentioning
confidence: 99%
“…Such a mode of action of E‐MC in vascular tissue differs from the one that was reported previously in isolated tracheal smooth muscles. In fact, in the latter preparations, both EOOM and its main constituent E‐MC more potently inhibited cholinergic‐induced contractions than KCl‐induced contractions . This suggests that E‐MC acts against contractile responses that preferentially recruit pharmacomechanical coupling in rat airway tissues, a finding that is clearly different from other essential oils and volatile compounds that preferentially act on electromechanically induced contractions …”
Section: Discussionmentioning
confidence: 90%
“…Pharmacological reports on MC are scarce, but recent studies from our group have found interesting pharmacological effects of the E ‐ and Z ‐isomers of MC on smooth muscle tissues in rats . In isolated tracheal smooth muscle preparations, both the essential oil of O. micranthum (EOOM) and its main constituent E‐MC (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Kim et al (1995), alguns tem a capacidade de inibir bactérias de origem alimentar e prolongar a vida de prateleira de alimentos processados. Além disso, estudos apontam que essas substâncias possuem efeito antifúngico (Machado et al, 2013), anti--inflamatórios, antinociceptivo e antiespasmódico (Daniel et al, 2009;Adorjan & Buchbauer, 2010;Pinho et al, 2012), atividades antitumoral (Wang et al, 2012;Quassinti et al, 2013) e inseticida (Lima et al, 2014). Portanto, é necessária a implantação de políticas públicas de conscientização, voltadas para o melhor manejo do extrativismo sustentável desse bioma, com vistas à preservação.…”
Section: Fonte: Adaptado De Sebrae (2007)unclassified